กรอบความสมดุลทางดนตรีศึกษาของประเทศไทย วาดวยการลดกระแสนิยมในการแสดงดนตรีและฟนฟูการสอนดนตรี เพื่อบมเพาะความคิด ความละเอียดออน และคุณธรรม How can music education in Thailand today be framed in a way which better balances the narrow modern interest in - อุทัยสุข Udtaisuk ดนีญา Dneya (Journal of Fine and Applied Arts Khon Kaen University, 2016)
Music education today in Thailand is facing a number of challenges to do with a conﬂ ict or gap between modern and traditional approaches to and aspects of music education. The negative consequences of modern interest in performing outcomes could lessen both students’ cognitive development opportunity and artistic sensitivity nourishment. To achieve a better balance would enhance music education today in Thailand in terms of expectations about improving the teaching and learning in the music education classroom. Therefore this paper will discuss such a challenge in terms of a better linked approach, combining Eurhythmics and traditional Thai music teaching, in order to create a music education approach which might be adapted to local context. ดนตรีศึกษาในประเทศไทยในปจจุบันกําลังเผชิญกับความทาทายในเรื่อง ของความไมสมดุลระหวางการปฏิบัติตามความนิยมสมัยใหมกับการปฏิบัติตาม แนวทางและการใหคุณคาตอดนตรีที่สืบทอดมาจากอดีต การที่ความนิยมสมัยใหม ไดใหความสําคัญกับทักษะการบรรเลงดนตรีในฐานะผลลัพธที่พึงประสงคของการ เรียนดนตรีมากขึ้นทุกทีอาจสงผลกระทบใหผูเรียนขาดสิ่งแวดลอมที่อํานวยตอการ พัฒนาทักษะทางปญญา และพลาดโอกาสในการบมเพาะความละเอียดออน การหา จุดสมดุลระหวางการใหคุณคากับดนตรีในอดีตและการตีคาในปจจุบันไดจะสามารถ พัฒนาการสอนดนตรีในชั้นเรียนของประเทศไทยได บทความวิชาการนี้จะนําเสนอ รูปแบบปญหาหรือความทาทายที่เกิดขึ้น และการนําเสนอการเชื่อมโยงหลักการยูริธึมมิกสมาผสมผสานกับการสอนดนตรีไทยแบบมุขะปาฐะหรือแบบดั้งเดิมเพื่อให เหมาะสมกับบริบทสังคมไทย